1999
DOI: 10.1046/j.1365-2591.1999.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde release from root‐canal sealers: influence of method

Abstract: From the results of this study it is difficult to define a standardized in-vitro test that can be applied universally for the definitive determination of formaldehyde release from endodontic sealers. Prediction of in-vivo formaldehyde release from endodontic sealers is difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
1
16
0
6
Order By: Relevance
“…Because of the chemistry of the epoxy amines, the material no longer releases toxic substances like formaldehyde (Leonardo et al . 1999) compared to AH26 (Koch 1999).…”
Section: Introductionmentioning
confidence: 91%
“…Because of the chemistry of the epoxy amines, the material no longer releases toxic substances like formaldehyde (Leonardo et al . 1999) compared to AH26 (Koch 1999).…”
Section: Introductionmentioning
confidence: 91%
“…[12]. Cohen et al (1998) and Koch (1999) IJOMEH 2014;27(5) 799 Vellinge, Sweden). Lack of anti-allergic medication constituted a mandatory condition before placing the patches and during the testing.…”
Section: Introductionmentioning
confidence: 99%
“…As a result they have demonstrated that all materials showed the highest release of formaldehyde in the case of freshly mixed samples [13,14]. Both MMA and formaldehyde have been often associated with local allergic reactions in the patients' oral mucosa as a result of contact with prosthetic and orthodontic devices [15].…”
mentioning
confidence: 99%
“…The remaining methods involve an initial reaction with colorimetric reagents to form formaldehyde adducts which are then analyzed by their ultraviolet absorption spectra, generally after removing other components by HPLC (Cohen et al . , Koch , Koch et al . ).…”
Section: Quantification Of Formaldehydementioning
confidence: 99%
“…In another study, Koch () determined that 8 mg of formaldehyde was produced per gram of AH 26 immediately after mixing and this then reduced to <1 mg g −1 after 48 h. Utilizing the highest formaldehyde release (8 mg formaldehyde g −1 ), the amount of formaldehyde released in a typical root canal filling with 7.5 mg sealer would be 0.06 mg of formaldehyde, which is 1/40 of the normal endogenous levels in all humans and 1/175 of the WHO () daily intake value. The formaldehyde amount falls to zero after 2 weeks as discussed earlier.…”
Section: Quantification Of Formaldehydementioning
confidence: 99%